2017
DOI: 10.1002/humu.23214
|View full text |Cite
|
Sign up to set email alerts
|

Rare deleterious variants in GRHL3 are associated with human spina bifida

Abstract: Neural tube defects, including spina bifida, are among the most common birth defects caused by failure of neural tube closure during development. They have a complex etiology involving largely undetermined environmental and genetic factors. Previous studies in mouse models have implicated the transcription factor Grhl3 as an important factor in the pathogenesis of spina bifida. In the present study, we conducted a resequencing analysis of GRHL3 in a cohort of 233 familial and sporadic cases of spina bifida. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 34 publications
1
26
0
1
Order By: Relevance
“…This variant leads to an arginine-to-cysteine substitution (NP_002327.2: p.Arg391Cys) in an evolutionarily conserved DNA-binding domain (figure 5). This change has been reported as a de novo variant in two patients, one with a CLP and lip pits,22 the other with spina bifida 2322 24…”
Section: Resultsmentioning
confidence: 82%
“…This variant leads to an arginine-to-cysteine substitution (NP_002327.2: p.Arg391Cys) in an evolutionarily conserved DNA-binding domain (figure 5). This change has been reported as a de novo variant in two patients, one with a CLP and lip pits,22 the other with spina bifida 2322 24…”
Section: Resultsmentioning
confidence: 82%
“…In a previous study, the occurrence of NTDs in curly tail mice and knockout mice showed the full penetrance of spina bifida, which suggested Grhl3 as a candidate gene for NTDs (Gustavsson et al, ). In humans, a study found several rare variants of GRHL3 in 233 familial and sporadic spina bifida patients in an Italian population (Lemay et al, ). In our study, we found that rs2486668 increased the risk for spinal and encephalic NTDs in a Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, evidence from animals has demonstrated that the Grhl3 gene is essential for spinal neurulation (De Castro, Hirst, et al, ). A population study conducted using a whole‐exome sequencing (WES) method in 233 Italian cases of spina bifida found two novel truncating variants and five rare missense variants of GRHL3 (Lemay et al, ). However, the role of GRHL3 in human NTDs has only been explored for spina bifida subtype, and the associations between genetic variants and other phenotypes in human populations need to be examined.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our group has previously conducted whole exome sequencing (WES) in 43 trios affected with severe forms of NTDs (mainly MMC and anencephaly) and identified an important role for de novo variants in their etiology. We also previously used WES in three families each with two MMC cases as well as molecular inversion probe sequencing in a larger cohort, and we demonstrated a strong implication of GRHL3 (Grainyhead Like Transcription Factor 3; OMIM *608317) in the etiology of MMC (Lemay et al., ; Lemay et al, ). In our previous WES studies, we aimed at investigating the role of highly deleterious variants, defined as frameshift, stop, or splicing variants, in the causation of open and severe NTD (mainly MMC).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous WES studies, we aimed at investigating the role of highly deleterious variants, defined as frameshift, stop, or splicing variants, in the causation of open and severe NTD (mainly MMC). In this study, we conducted WES in five new families affected with both forms of open and closed NTDs and we reassessed the previously published cohorts consisting mainly of open MMC (Lemay et al., ; Lemay et al, ). WES data were analyzed using a biased candidate gene approach and an unbiased genetic burden approach.…”
Section: Introductionmentioning
confidence: 99%